Analysis of Garbage Management on board MV. HL Samcheonpo - Prasetyo, Yosep Hilwanto; Firdaus, Muhammad Imam; Rahayu, Trisnowati; Prasetyo, Anugrah Nur (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The research issues raised by what methods can be used to maximize the implementation of garbage management on board, while the aim of the research is to provide suggestion to minimize this problem. The research method used is a qualitative method while using the Miles and Huberman as approaching method to process data and then the results will be presented based on the objectives to be achieved. The data analysis techniques used including collecting primary data through observation, interviews and documentation as well as secondary data from the ship's archives. The theoretical basis used including theories about the marine pollution, garbage management, international rules governing garbage management on ships, supporting tools used to maximize garbage management, and ship operational standards regarding garbage management are also analyzed to support the research results. The results of this study found that the lack of implementation of waste management procedures on board ships is caused by the crew's low awareness regarding these procedures, leading to garbage accumulation and highlighting the need for supervision and education by officers in the implementation of waste management procedures.